Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.17576/gema-2018-1804-01
|View full text |Cite
|
Sign up to set email alerts
|

Academic Word List Knowledge of Malaysian ESL Undergraduates

Abstract: Academic words are specialised vocabulary of academic texts. The knowledge of these words is vital for comprehension and communication purposes, particularly among university students, to enable them to engage with authentic complex input, such as textbooks and journal articles. Limitation of academic vocabulary in their mental lexicon may restrict students 'comprehension to grasp the academic concepts they are learning. The current study investigated Malaysian English as a Second Language (ESL) undergraduates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…These were considered adequate percentages to ensure participants' comprehension (Hu &Nation 2000). Among all of the academic words, 12 words were among the least known academic words by ESL undergraduate students based on a study conducted by Sulaiman, Salehuddin and Khairuddin (2018). To facilitate the reading comprehension of the academic texts, glosses of four academic words were inserted on the right margin of the text.…”
Section: Reading Materialsmentioning
confidence: 99%
“…These were considered adequate percentages to ensure participants' comprehension (Hu &Nation 2000). Among all of the academic words, 12 words were among the least known academic words by ESL undergraduate students based on a study conducted by Sulaiman, Salehuddin and Khairuddin (2018). To facilitate the reading comprehension of the academic texts, glosses of four academic words were inserted on the right margin of the text.…”
Section: Reading Materialsmentioning
confidence: 99%
“…The presentation of new strategies through various tasks has fostered effective vocabulary learning and helped the students to become autonomous learners (Amiryousefi, 2015) as the learners at tertiary level need to be independent in conducting self-directed learning (Sulaiman et al, 2018). The current study has also bridged the gap between research and classroom practice by devising strategies and learning modules out of the theoretical Model.…”
Section: Resultsmentioning
confidence: 94%
“…Unlike L1 speakers, L2 speakers are not regularly being exposed to the large vocabulary of their target language Mohd Nordin et al, 2015). This is because not all of the words in the L2 vocabulary are relevant in the L2 learners' daily conversation (Sulaiman, Salehuddin & Khairudin, 2018). Alqahtani (2015), for example, highlighted that in the majority of cases, learners tend to recycle their vocabulary usage in their daily conversation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Nadarajan (2011) had earlier found that L2 learners often failed to select more precise words in their production tasks. This, according to Nadarajan (2011) and Sulaiman et al (2018), happened because although learners may have internalized larger and complex vocabulary through formal learning, they may not have understood how the words should be used in their writing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation